1982
DOI: 10.1002/pol.1982.170200926
|View full text |Cite
|
Sign up to set email alerts
|

Radiation‐induced oxidation of polyethylene, ethylene–butene copolymer, and ethylene–propylene copolymer

Abstract: Oxygen consumption and yield of oxidation products during γ‐irradiation were studied on five types of polyethylene (PE), ethylene–butene copolymer (EB), and ethylene–propylene copolymer (EPR) using gas chromatography, mass spectrography, and high‐resolution NMR. Samples were irradiated in oxygen under pressure from 0 to 500 torr by 60Co γ‐rays up to 20 Mrad at 22–25°C. In enough oxygen, oxygen consumption and yield of oxidation products are independent of oxygen pressure for low‐density PE, EB, and EPR. The G … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 15 publications
4
8
0
Order By: Relevance
“…These experiments determined that the G value for hydrogen in HDPE is 3.3 molecules per 100 eV, which is in good agreement with our previous values of 3.0–3.39 and the literature values of 3.0–4.4 18–25. For PP, the G values in the literature vary between 2.6 and 2.9 molecules per 100 eV for isotactic or atactic polymers 26–28.…”
Section: Resultssupporting
confidence: 91%
“…These experiments determined that the G value for hydrogen in HDPE is 3.3 molecules per 100 eV, which is in good agreement with our previous values of 3.0–3.39 and the literature values of 3.0–4.4 18–25. For PP, the G values in the literature vary between 2.6 and 2.9 molecules per 100 eV for isotactic or atactic polymers 26–28.…”
Section: Resultssupporting
confidence: 91%
“…137,231,392,1054,1112 Hydrogen abstraction by polymer alkoxy (PO·) and hydroxy (HO·) radicals from the photocleavage of hydroperoxy groups in 9 polypropylene occurs with 50% probability at methyl groups. Several studies have shown that branched polyethylenes oxidize more rapidly than their linear analogues because of the presence of the tertiary C-H site at each branch point.…”
Section: Hydrogen Abstractionmentioning
confidence: 99%
“…This result is also confirmed by the G 0 (CO 2 ) of the different materials, which were also far less important for XLPE M2(Irg1076), XLPE M4(Irg1076-IrgPS802), and XLPE M7(Irg1076-IrgPS802-ATH50) than for XLPE M1, XLPE M3(IrgPS802), XLPE M5(ATH25), and XLPE M6(ATH50). This gas is formed by decomposition of oxidized species—stable or not [ 41 , 42 , 43 ]—and these oxidized species are necessarily formed by mechanisms that require prior oxygen incorporation in the polymer chain. The less oxygen incorporated in the polymer, the less carbon dioxide release possible.…”
Section: Resultsmentioning
confidence: 99%